Readiness toward M-learning implementation during pandemic: Secondary high school teachers and student's perception - Sherla Sepsa Rosiva; Dedi Kuswandi; Yerry Soepriyanto (Jurnal Penelitian Ilmu Pendidikan, 2022)
During the COVID-19 pandemic, almost all secondary high schools (SMP) in Indonesia implemented distance learning to minimize face-to-face meetings by utilizing technological developments, especially through mobile phones. However, several junior high schools still encounter obstacles that prevent them from implementing distance learning, such as the lack of readiness of devices and adequate internet connections. This study uses an exploratory research design to determine the readiness of teachers and junior high school students to use their mobile phones as a learning tool that can be implemented during a pandemic. The questionnaire given is in the form of questions that link the use of mobile devices to the successful implementation of m-learning adoption in secondary high school. This questionnaire was adopted by Miglani and Awadhiya (2017). Survey responses are based on a five-point Likert-type scale: (1) strongly disagree; (2) disagree; (3) neutral; (4) agree; (5) strongly agree. The survey was distributed to teachers and students of SMP in Malang City. The total respondents are 32 teachers and 206 students. The results show that all teachers (100%) and students (99%) are ready to own a mobile device and most teachers (89%) and students (85%) have acquired the basic skill requirements for m-learning. This study recommends that teachers and students improve their advanced skills in using mobile phones to achieve learning objectives. Teachers can participate in available training and workshops, while students should be better prepared to use mobile phones to learn, create and share knowledge. Kesiapan implementasi M-learning selama masa pandemi: Persepsi guru dan siswa sekolah menengah pertamaSelama pandemi covid-19, hampir seluruh sekolah menengah pertama (SMP) di Indonesia menerapkan pembelajaran jarak jauh untuk meminimalisir pertemuan tatap muka dengan memanfaatkan perkembangan teknologi, terutama melalui ponsel. Namun, beberapa sekolah menegah pertama masih mendapatkan kendala sehingga tidak dapat menerapkan pembelajaran jarak jauh, seperti kurangnya kesiapan perangkat serta koneksi internet yang memadai. Penelitian ini menggunakan desain penelitian eksploratif untuk mengetahui kesiapan guru dan siswa SMP terhadap penggunaan ponsel mereka sebagai alat pembelajaran yang dapat diimplementasikan selama pandemi. Kuesioner yang diberikan berupa pertanyaan yang menghubungkan penggunaan perangkat seluler untuk keberhasilan penerapan adopsi m-learning di sekolah menengah pertama. Kuesioner ini diadopsi dari Miglani dan Awadhiya (2017). Jawaban survei didasarkan pada skala tipe Likert lima poin: (1) sangat tidak setuju; (2) tidak setuju; (3) netral; (4) setuju; (5) sangat setuju. Survei dibagikan kepada guru dan siswa SMP di Kota Malang. Total responden yaitu 32 guru dan 206 siswa. Hasil menunjukkan bahwa seluruh guru (100%) dan siswa (99%) memiliki kesiapan dalam kepemilikan perangkat seluler dan sebagian besar guru (89%) dan siswa (85%) telah memperoleh persyaratan keterampilan dasar untuk m-learning. Penelitian ini merekomendasikan kepada guru dan siswa untuk meningkatkan keterampilan lanjutan mereka dalam penggunaan ponsel untuk mencapai tujuan pembelajaran. Guru dapat mengikuti pelatihan maupun lokakarya yang tersedia, sedangkan siswa harus lebih siap menggunakan ponsel untuk belajar, membuat dan berbagi pengetahuan.